Animal Production With Restrictive Use of Antibiotics to Contain Antimicrobial Resistance in Sweden—A Qualitative Study - Björkman, Ingeborg; Röing, Marta; Sternberg Lewerin, Susanna; Stålsby Lundborg, Cecilia; Eriksen, Jaran (Frontiers in Veterinary Science, 2021)
Antibacterial resistance (ABR), is a growing global threat to human and animal health. Efforts to contain ABR are urgently needed. This qualitative interview study explored perceptions of work to contain ABR among stakeholders in food animal production in Sweden, with focus on broiler production. Semi-structured interviews were carried out with a strategic sample of 13 stakeholders in different parts of production, from professionals at policy level, veterinary authorities, to poultry farmers and poultry veterinarians. Conventional inductive content analysis was used for data analysis. A latent theme, “Working in unison”, emerged, based on the consistency expressed by the informants when they discussed ABR, use of antibiotics, and animal health management. This theme was built on four domains representing the content of the interviews: Knowledge and engagement; Cooperation; Animal health concept; and Development in balance with economic prerequisites. According to the informants, ABR has not been an isolated issue in Sweden but has been included in a tradition of animal health and welfare, and actions have been driven by the industry or by government regulations. Veterinarians described how they worked closely with farmers. Farmers felt involved in the development of animal health management methods. The One Health concept was well known among stakeholders at national level but not at farm level. Close cooperation between stakeholders seems to facilitate development of animal production with low use of antibiotics.